2012
DOI: 10.1093/jb/mvs025
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 8-anilinonaphthalene 1-sulphonate (ANS) and human matrix metalloproteinase 7 (MMP-7) as examined by MMP-7 activity and ANS fluorescence

Abstract: Human matrix metalloproteinase 7 (MMP-7) is the smallest matrix metalloproteinase. It plays important roles in tumour invasion and metastasis. 8-Anilinonaphthalene 1-sulphonate (ANS) is a fluorescent probe widely used for the analysis of proteins. It emits large fluorescence energy when its anilinonaphthalene group binds with hydrophobic regions of protein. In this study, we analysed the interaction of ANS and MMP-7. At pH 4.5-9.5, ANS inhibited MMP-7 activity in the hydrolysis of (7-methoxycoumarin-4-yl)acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…MMP-7/matrilysin is an enzyme that degrades collagens I, III, IV and V, fibronectin, vitronectin, laminin and elastin [47] and is expressed in variety of cancers including colon, prostate, esophageal and HNSCCs [48,49,50,51,52]. Gene expression analyses also show that MMP-7 is significantly overexpressed in almost all HNSCC datasets (Figure 2 and Table 1, Table 2, Table 3, Table 4 and Table 5).…”
Section: Roles Of Mmps In Hnsccsmentioning
confidence: 99%
“…MMP-7/matrilysin is an enzyme that degrades collagens I, III, IV and V, fibronectin, vitronectin, laminin and elastin [47] and is expressed in variety of cancers including colon, prostate, esophageal and HNSCCs [48,49,50,51,52]. Gene expression analyses also show that MMP-7 is significantly overexpressed in almost all HNSCC datasets (Figure 2 and Table 1, Table 2, Table 3, Table 4 and Table 5).…”
Section: Roles Of Mmps In Hnsccsmentioning
confidence: 99%
“…MMP7 is a Wnt-targeting gene that has been detected in several cancers, such as prostate, colon, stomach, lung, and breast [13-17] and degrades components of the extracellular matrix (ECM), including collagens (I, III, IV, and V), fibronectin, vitronectin, laminin, and elastin [18]. In the oral region, Chuang et al demonstrated that MMP7 is closely related to invasion in OSCCs of buccal mucosa [19].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-7 is the smallest of the matrix metalloproteinases (MMPs) in size, with 28 kDa latent pro-form, and the mature form being 19 kDa [ 14 ]. MMP-7 is composed of a five-stranded β-sheet and three α-helices, with zinc-containing active domain, and other zinc and calcium ions necessary for structural stability [ 15 ].…”
Section: Introductionmentioning
confidence: 99%